Literasi Keuangan Syariah dan Motivasi Berwirausaha: Strategi Penguatan Pengelolaan Keuangan Berbasis Nilai Islami - Armadiana, Rodiyah; Aslikhah; Sukamto (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
This study aims to analyze the relationship between Islamic financial literacy and entrepreneurial motivation in strengthening students’ financial management skills at Universitas Yudharta Pasuruan. The disparity in financial literacy levels across Indonesian regions highlights the importance of continuous education and training in Islamic-based finance. Although awareness of Islamic economics is increasing, many students still lack adequate understanding of Islamic financial management principles, which may affect their future financial well-being. This research employed a qualitative approach using in-depth interviews and observations of students with entrepreneurial interests. The findings reveal that entrepreneurial motivation serves as a key factor encouraging students to adopt ethical and responsible financial management practices. However, the application of Islamic financial values remains largely conceptual and not yet fully integrated into entrepreneurial activities. Therefore, structured and practical Islamic financial literacy programs are necessary to enhance students’ competencies in managing sustainable and sharia-compliant businesses.